Influence of fatigue on construction workers' physical and cognitive function. (20th February 2015) - Zhang, M.; Murphy, L. A.; Fang, D.; Caban-Martinez, A. J.
Abstract: Background: Despite scientific evidence linking workers' fatigue to occupational safety (due to impaired physical or cognitive function), little is known about this relationship in construction workers. Aims: To assess the association between construction workers' reported fatigue and their perceived difficulties with physical and cognitive functions. Methods: Using data from a convenience sample of US construction workers participating in the 2010–11 National Health Interview Survey two multivariate weighted logistic regression models were built to predict difficulty with physical and with cognitive functions associated with workers' reported fatigue, while controlling for age, smoking status, alcohol consumption status, sleep hygiene, psychological distress and arthritis status. Results: Of 606 construction workers surveyed, 49% reported being 'tired some days' in the past 3 months and 10% reported 'tired most days or every day'. Compared with those feeling 'never tired', workers who felt 'tired some days' were significantly more likely to report difficulty with physical function (adjusted odds ratio [AOR] = 2.03; 95% confidence interval [CI] 1.17–3.51) and cognitive function (AOR = 2.27; 95% CI 1.06–4.88) after controlling for potential confounders. Conclusions: Our results suggest an association between reported fatigue and experiencing difficulties with physical and cognitive functions in construction workers.